2008
DOI: 10.1161/circulationaha.107.717033
|View full text |Cite
|
Sign up to set email alerts
|

Preventing Heart Disease in the 21st Century

Abstract: W e could prevent 90% of heart attacks. Such a claim would have seemed outrageous in the 1960s, as the coronary heart disease (CHD) epidemic reached new heights and accounted for one third of all deaths in the United States and most other developed countries. 1 The identification of conditions that predicted the probability of CHD (known as "risk factors") stimulated hope that modification of these risk factors would reduce the frequency of CHD. Long before this idea was validated in clinical trials, individua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
163
0
8

Year Published

2010
2010
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 467 publications
(176 citation statements)
references
References 134 publications
(98 reference statements)
5
163
0
8
Order By: Relevance
“…Comparing our study observations, out of 105 patients 52.4% were uneducated, 12.4% with primary education, 28.6% with secondary education, 2.9% with pre-university and 3.8% with degree education. In addition, in another study, 71.8% were having an occupation 8 and a fewer women have household incomes. 3 The results of our study reveals that, 6.6% were unemployed and 13.3% were employed and about 93.3% of patients are aware about high blood pressure and diabetes as a risk factor which is followed by smoking 85.7% and overweight 60% which can be compared with a study showing that 92% had a good knowledge on fatty food consumption, 83% were aware of smoking, 42% were aware about obesity as a risk factor and only 25% knows about the protective effect of exercise.…”
Section: Discussionmentioning
confidence: 88%
“…Comparing our study observations, out of 105 patients 52.4% were uneducated, 12.4% with primary education, 28.6% with secondary education, 2.9% with pre-university and 3.8% with degree education. In addition, in another study, 71.8% were having an occupation 8 and a fewer women have household incomes. 3 The results of our study reveals that, 6.6% were unemployed and 13.3% were employed and about 93.3% of patients are aware about high blood pressure and diabetes as a risk factor which is followed by smoking 85.7% and overweight 60% which can be compared with a study showing that 92% had a good knowledge on fatty food consumption, 83% were aware of smoking, 42% were aware about obesity as a risk factor and only 25% knows about the protective effect of exercise.…”
Section: Discussionmentioning
confidence: 88%
“…Mudanças na saúde pública associadas às transformações sociais e culturais também são necessárias para atingir a população como um todo. A participação dos pais e médicos em interação com os demais profissionais da saúde, educadores, cientistas e legisladores é fundamental para garantir a aplicabilidade das recomendações fornecidas pela diretriz 22,23 .…”
Section: Discussionunclassified
“…Additional research has indicated that pathological changes, such as markers of atherosclerosis and changes in left ventricular morphology, measured concurrently or in Kelly RK et al . Youth blood pressure and adulthood outcomes adulthood, are associated with elevated youth blood pressure [10][11][12][13][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55] . These changes are largely asymptomatic and are detectable prior to signs of end-organ damage such as nephropathy and retinopathy.…”
Section: Importance Of Identifying Youth Hypertensionmentioning
confidence: 99%